Perceived Risk And Trust To Maximize Purchase Intention Through Planned Behavior Theory - Nabil Maulana; Endy Gunanto Marsasi (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2024)
This study aims to determine the role of risk perception, perceived benefits, and trust in optimizing purchase intentions based on the theory of planned behaviour. The theory of planned behaviour is used to understand human behaviour, which includes attitudes, subjective norms, beliefs, and behaviour. The object of this research is expedition services and the subject of the research is consumers of expedition services on the island of Java. This study uses a quantitative approach by collecting data from 216 expedition service consumers. The study shows that risk perception and trust have a significant impact. This study also found that trust influences purchase intentions. Persuasion has no significant impact on behaviour towards the usage of expeditions. The study uses a vital variable, namely, the perceived risk directly related to the use of the expedition. These findings provide important insights for companies to develop marketing strategies that utilize the power of risk perception and benefit perception to build trust and increase purchase intentions.